Exploring the competencies perceived by the hospitality undergraduates in public and private universities - Mohamad, Siti Fatimah; Osman, Mohammad Nazrin; Che Ishak, Farah Adibah (Human Resource Management Academic Research Society, 2018)
Excellent academic performance does not ensure a job offer to the fresh graduates. Employers are now looking at the graduates’ competencies. There is a tense among undergraduates to compete in the battle of competencies, which are demanded by the industry. This study aimed to explore the competencies perceived by hospitality undergraduates in both public and private universities in Malaysia. The sample was selected using purposive and snowball sampling methods, where semi-structured interviews were conducted to the respondents. The findings of this study reveal eight core competencies perceived by the respondents: communication skill, lifelong learning and information management, teamwork skill, technical skill, moral and professional ethics, critical thinking and problem solving, leadership skill, and entrepreneurial skill. The most common skill delineated by the respondents was the communication skill, while the least was the entrepreneurial skill. This study is anticipated to give an understanding about the competencies obtained and possessed by the undergraduates, although there are various competencies infused in the curriculum. It is also expected by exploring the components of the skill, the effort to bridge the skill gap between university and industry will be less severe, which later enhance the quality of the fresh hospitality graduates.